Recursos retóricos para a construção de contexto em um editorial de jornal: um enfoque crítico da Linguística Sistêmico-Funcional - Bertelli, Adriana Baldas Kutz (2017)
The objective of this master's thesis is the critical examination of the role of language in the construction of context in the persuasive process present in the editorial entitled "O Quinto Centenário” (The Fifth Centenary), published in the newspaper Folha de S.Paulo, on 24.04.2000. The research has the theoretical-methodological support of Systemic-Functional Linguistics (SFL), which involves the notion of evaluation (MARTIN, 2000, 2003), the ethical, aesthetic and emotional evaluation – in the construction of a "textual world" that contributes to the context construction. Scholars, who deal with language and text (although the fact has been clear to rhetoric practitioners for millennia), have accepted it, that the implicit presentation of content may facilitate persuasion of the audience. Language works in social processes, actively constructing context, and, at the same time, it is its expression (LUKIN, 2013). In this process, meanings are influenced by the cultural context – genre – and by the situational context – register – in which they are exchanged (HALLIDAY, 1994, 2004). Language is a "way of action" and not just an "expression of thought" as it relates to the relationships between text, context and their extensions (MALINOWSKI, 1935). Relating to these questions, research also has the support of Critical Linguistics (FOWLER, 1991), for which any aspect of the linguistic structure carries ideological significance. For sociologists, journalistic news is a commodity in the business process of providing forms of consciousness. The research, of a critical nature, answers the following questions: (a) What "context-building" work does the editorial genre examined do? (B) What role does the construction of context play in the persuasive process that runs through the editorial? The results show the construction of a context that is based on the knowledge of the reader, present in its frame, in a process of intersubjectivity, which makes it complicit in the intentions of the newspaper. Thus, the editorial constructs a discourse that is coherent in this "textual world" (DOWNING 2003), although unilateral in the underlay of the text, made by the news provider in line with ideas of controlling groups in an industrial-capitalist society, because the newspaper is an industry with its own commercial interests